Dissolution of Chalcopyrite in Presence of Chelating Agent and Hydrogen Peroxide - Turan, M. Deniz; Silva, J. Pedro; Sari, Z. Abidin; Nadirov, Rashid; Toro, Norman (Springer India, 2022)
Chelating agents (e.g., EDTA, titriplex III, etc.) are very important salts as they can take a complex form with metal ions. This study investigated usage of titriplex III in presence of hydrogen peroxide for metal extraction from chalcopyrite concentrate under various conditions such as conventional leaching, mechanical activation and ultrasound leaching. The results show that both titriplex and hydrogen peroxide are required for metal extraction from chalcopyrite concentrate. However, mechanical activation is an important parameter for increasing metal extraction, so that copper extraction increases to 83% from 47% after 30 min of grinding chalcopyrite by a high-energy grinding system. Metal extraction efficiency is improved by application of ultrasound to the leaching process. It is possible to obtain copper and iron extraction as 93% and 65%, respectively, under the following leaching conditions: mechanical activation time of 30 min, titriplex concentration of 100 g L-1, H2O2 concentration of 2 mol L-1, ultrasound power of 10%, leaching time of 90 min, leaching temperature of 45 degrees C and liquid-solid ratio of 25 mL g(-1).
Keywords: Leaching; Titriplex III; Mechanical activation; Chelating; Ultrasound; Hydrogen peroxide; Copper